The acute inflammatory response after trauma is heightened by frailty: A prospective evaluation of inflammatory and endocrine system alterations in frailty. Issue 1 (July 2019) - Palmer, James; Pandit, Viraj; Zeeshan, Muhammad; Kulvatunyou, Narong; Hamidi, Mohammad; Hanna, Kamil; Fain, Mindy; Nikolich-Zugich, Janko; Zakaria, El-Rasheid; Joseph, Bellal
Abstract : BACKGROUND: Frailty is a geriatric syndrome characterized by decreased physiological reserves, increased inflammation, and decreased anabolic-endocrine response. The biomarkers associated with frailty are poorly understood in trauma. The aim of this study was to analyze the association between frailty and immune: IL-1β, IL-6, IL-2Rα, tumor necrosis factor (TNF)-α, and endocrine biomarkers: insulin-like growth factor-1 and growth hormone in trauma patients. METHODS: We conducted a 1-year (2017–2018) prospective analysis of geriatric (≥65 years) trauma patients admitted to our Level I trauma center. Frailty was measured using the trauma-specific frailty index (TSFI) and blood samples were collected within 24 hours of admission. Patients were stratified into two groups: frail (TSFI > 0.25) and nonfrail (TSFI ⩽ 0.25). We then measured the levels of immune and endocrine biomarkers by a colorimetric output that was read by a spectrophotometer (Quantikine ELISA). The outcome measures were the levels of the immune and endocrine markers in the two groups. Multivariable linear regression was performed. RESULTS: A total of 100 geriatric trauma patients were consented and enrolled. The mean age was 77.1 ± 9.8 years and 34% were female. Thirty-nine (39%) patients were frail. Frail patients were more likely to present after falls ( p = 0.01 ). There was no difference in age ( p = 0.78 ), sex ( p = 0.77 ), systolic blood pressure ( p = 0.16 ), and heart rate ( p = 0.24 ) between the two groups. Frail patients had higher levels of TNF-α ( p = 0.01), IL-1β ( p = 0.01), and IL-6( p = 0.01) but lower levels of growth hormone ( p = 0.03) and insulin-like growth factor-1 ( p < 0.04) compared with nonfrail patients. There was no difference in the level of IL-2Rα ( p = 0.25 ). On regression analysis, frailty was positively correlated with the levels of proinflammatory biomarkers, that is, TNF- α, IL-1 β, and IL-6 and negatively correlated with endocrine biomarkers. CONCLUSION: This study supports the association between frailty and immune and endocrine markers. Frailty acts synergistically with trauma in increasing the acute inflammatory response. Moreover, frail patients have lower levels of anabolic hormones. Understanding the inflammatory and endocrine response in frail trauma patients may result in better therapeutic strategies. Abstract : Supplemental digital content is available in the text.